Sustainable synthesis of porous reaction-formed SiC ceramics through siliconization of waste fabric-derived carbon preforms using reclaimed Si wafers - Das, Dulal; Kim, Jinha; Kim, Heeju; Lee, Sungho; Jeong, Hyeondeok (한국탄소학회, 2026)
Although porous SiC ceramics have been applied across various industries, their high cost limits broader and more extensive utilization. In this study, porous reaction-formed SiC ceramics were fabricated using waste fabric and discarded silicon wafer waste as carbon and silicon sources, respectively. Three types of porous carbon preforms with ∼77% porosity were prepared by varying the initial ratios of waste fabric and furfuryl alcohol. The influence of waste fabric content on the microstructure and mechanical properties of the porous carbon preform was systematically investigated. Higher waste fabric content led to the formation of a more uniform, network-like microstructure, free of large, dense carbon residues. This microstructural refinement enhanced the conversion efficiency of carbon to SiC during the infiltration process. The optimal performance was achieved with a preform containing 75 wt% waste fabric, infiltrated with molten silicon at 1500 °C for 1 h. The resulting SiC ceramics exhibited a compressive strength of 51.4 MPa at 59.4% porosity, surpassing that of porous reaction-bonded SiC ceramics. This approach, involving molten Si infiltration into waste-derived, low-cost carbon preforms, offers a cost-effective and environmentally sustainable route for fabricating high-performance porous carbon structures and porous SiC ceramics for diverse industrial applications.